New interlocking inter-module connection for modular steel buildings: Experimental and numerical studies. (1st November 2019) - Lacey, Andrew William; Chen, Wensu; Hao, Hong; Bi, Kaiming
Highlights: A new interlocking inter-module connection is proposed for modular steel buildings. Structural bolts are combined with interlocking elements called locating pins. The shear force-slip behaviour is investigated and an empirical model is proposed. Slip resistance depends on the slip factor, bolt preload, and bolt hole tolerance. The locating pins provide additional shear resistance after the initial slip. Abstract: To improve the constructability and performance of modular buildings, a number of inter-module connections have been developed, each with their own associated advantages and disadvantages. Interlocking inter-module connections have emerged as a promising type of improvement; however, it is not clear how to provide the required installation tolerance without allowing slip. At the same time, the existing model for the shear force-slip behaviour is known to be inadequate. This study introduces a novel interlocking inter-module connection which combines structural bolts with interlocking elements to improve the constructability and shear force-slip behaviour. An experimental study was conducted to investigate the shear force-slip behaviour of the proposed connection. The effects of the interlocking elements, bolt preload, hole tolerance, and fabrication and assembly tolerance on the shear behaviour are evaluated and discussed. Numerical simulations were carried out to support the experimental program, following which the distinguishing features of the force-slip behaviour were examined, and an empirical model was proposed.